The effect of green marketing on sustainable développement Case study institution SONATRACH - MOKHTARI, ABDULDJABAR; ZAOUI, CHARAF (Journal of Excellence for Economics and Management Research, 2020)
this study aims to know the effect of green marketing on sustainable développement, both are of importance on the part of businessemen and gouvernements, thanks to their role in achieving a balance between profitability and environmental protection. We have conducted a field study for the Sonatrach Foundation, where this study reached several results, the most important of which is that the Sonatrach Corporation seeks to achieve sustainable development through its industrial activities by: reducing gas emissions, paying attention to recycling of its waste, managing its waste .... By producing Liquefied Petroleum Gas (GPL) which is environmentally friendly.